Association of Smartphone‐Recorded Steps Over Years and Change in Cardiovascular Risk Factors Among Working‐Age Adults - Rikuta Hamaya; Masaki Mori; Kuniaki Miyake; I‐Min Lee (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Few data exist on long‐term steps and their relation to changes in cardiovascular disease risk factors. We aimed to examine the associations using long‐term smartphone‐recorded steps. Methods and Results The present analysis made use of data from 2 national databases and a commercial app database. We evaluated the associations between smartphone‐recorded daily steps over 2 years and 2‐year changes in the cardiovascular disease risk factors. A total of 15 708 participants with mean (SD) age of 44.1 (9.5) and 23.5% women were included. After adjustment for potential confounders, differences in weight were almost linearly associated with 2‐year steps in men (estimate [SE] per 1000 steps/d: −0.33 [0.029] kg), and inversely related only above 5000 steps/d in women (−0.18 [0.054] kg). An inverse linear association with systolic blood pressure was observed in men (−0.34 [0.097] mm Hg) but not in women. Greater steps were associated with change in high‐density lipoprotein cholesterol and triglycerides (0.61 [0.068] and −3.4 [0.61] mg/dL in men; 0.64 [0.17] and −2.3 [0.67] mg/dL in women), while changes in low‐density lipoprotein cholesterol were evident in men only (−0.59 [0.17] mg/dL). A significant negative association with hemoglobin A1c was observed only in women (−0.012 [0.0043] %). Conclusions In a large cohort of Japanese adults, smartphone‐recorded steps over years were associated with beneficial changes in cardiovascular disease risk factors, with some differences between men and women in the associational patterns. The findings support the benefit of long‐term physical activity for cardiovascular disease health and suggest a useful role of smartphone‐recorded steps for monitoring cardiovascular disease risk over the long term.